The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1371/journal.pone.0296420
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope chemistry reveals plant-dominant diet among early foragers on the Andean Altiplano, 9.0–6.5 cal. ka

Jennifer C. Chen,
Mark S. Aldenderfer,
Jelmer W. Eerkens
et al.

Abstract: Current models of early human subsistence economies suggest a focus on large mammal hunting. To evaluate this hypothesis, we examine human bone stable isotope chemistry of 24 individuals from the early Holocene sites of Wilamaya Patjxa (9.0–8.7 cal. ka) and Soro Mik’aya Patjxa (8.0–6.5 cal. ka) located at 3800 meters above sea level on the Andean Altiplano, Peru. Contrary to expectation, Bayesian mixing models based on the isotope chemistry reveal that plants dominated the diet, comprising 70–95% of the averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Despite the evidence, many humans resist this change, often citing a presumed ‘naturalness’ of the meat diet along with respect for tradition as reasons for such resistance. This transition may be facilitated by people learning that not only were early humans consuming predominantly plant-based foods [ 107 ], but that our own closer ancestors (from a hundred, two hundred, three hundred, etc., years ago) were embedded in a tradition that was a lot more nuanced than we have been led to believe. This tradition featured complex interspecies relations, and complicated interactions between human and nonhuman subjects, each with an interest in their own life and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evidence, many humans resist this change, often citing a presumed ‘naturalness’ of the meat diet along with respect for tradition as reasons for such resistance. This transition may be facilitated by people learning that not only were early humans consuming predominantly plant-based foods [ 107 ], but that our own closer ancestors (from a hundred, two hundred, three hundred, etc., years ago) were embedded in a tradition that was a lot more nuanced than we have been led to believe. This tradition featured complex interspecies relations, and complicated interactions between human and nonhuman subjects, each with an interest in their own life and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Hunter-gatherers have been described as individuals who do not intentionally modify the gene pool of exploited resources, as opposed to those who rely primarily on an agricultural or pastoralist subsistence [ 110 ]. The diets of hunter-gatherers can be inferred by dental morphology [ 111 ], stable isotope analysis [ 112 113 ], and analysis of faunal remains [ 114 ], and it is largely agreed that hunter-gatherers relied on a diverse range of foodstuffs which varied depending on geographical location and seasonal period [ 115 ]. Comparisons of ancient humans, Neanderthals and non-human primates showed that the composition of the core oral microbiome has remained stable for potentially millions of years, but the functions performed by oral microbiota have changed over time as they adapted to changing host diet [ 116 ].…”
Section: The Oral Microbiome Through the Agesmentioning
confidence: 99%